Cultural cooperation between nations as an important factor of sustainable social development of the region of Central and Eastern Europe in the European Union (for instance Poland and Lithuania) - Beata Adamczyk (Studia Ecologiae et Bioethicae)
Cultural and social cooperation among nations lived in East and Central Europe has been sprung up over many centuries. In the 20th century, the nations of the part of Europe were subjected to an attempt to standardize their national cultures by means of introducing the socialist realistic culture. At present the message of cultural cooperation is social and cultural integration. Relations between Poland and Lithuania can be an example for development of cooperation among the other countries of Central and Eastern Europe on the state and regional levels, as well as example for educational institutions and economic associations, the connected relations may become germs of cooperation and good-neighbourly relationship as well as in the perspective of social development of the region among the Baltic Sea, the Black Sea and the Adriatic Sea.